Beyond greed and grievance: feasibility and civil war - Collier, P; Hoeffler, A; Rohner, D (2009)
Civil war is the most prevalent form of large-scale violence and is massively destructive to life, society, and the economy. The prevention of civil war is therefore a key priority for international attention. We present an empirical analysis of what makes countries prone to civil war. Using a global panel data set we examine different determinants of civil war for the period 1960-2004. We find little evidence that motivation can account for civil war risk but we suggest that there is evidence to support our feasibility hypothesis: that where a rebellion is financially and militarily feasible it will occur.